Effect of ultrasound-guided scalp nerve block on hemodynamics and postoperative agitation in hypertensive cerebral hemorrhage craniotomy patients: a prospective randomized controlled study - Li, Bing; Cao, Zhifang; Huang, Junlong; Chen, Ying; Li, Zhihua; Wu, Weiming; Li, Chuntian; Qiu, Ting; Chen, Juncheng (Frontiers in Neurology, 2026)
ObjectiveThis study aims to investigate the impact of dexmedetomidine combined with ropivacaine scalp nerve block (SNB) on analgesic effects in patients undergoing craniotomy for hypertensive intracerebral hemorrhage (HICH).MethodsA prospective randomized controlled trial was conducted on 120 HICH patients who underwent craniotomy at Longyan First Affiliated Hospital of Fujian Medical University from May 2022 to April 2024. Patients were randomly divided into three groups: control group (A, no SNB), ropivacaine SNB group (B, 0.5% ropivacaine), and dexmedetomidine-ropivacaine SNB group (C, 0.5% ropivacaine + 0.5 μg/kg dexmedetomidine), with 40 patients in each group. Primary outcomes included intraoperative hemodynamic parameters [mean arterial pressure (MAP), heart rate (HR)], intraoperative anesthetic consumption, postoperative Visual Analogue Scale (VAS) scores, rescue analgesia requirements, and incidence of adverse reactions within 48 h postoperatively.ResultsGeneral characteristics were comparable among the three groups (p > 0.05). Compared with Group A, Groups B and C showed more stable intraoperative MAP and HR (p < 0.05), lower VAS scores at 6, 12, 24, and 48 h postoperatively (p < 0.01), reduced consumption of propofol and remifentanil (p < 0.01), delayed first rescue analgesia (p < 0.01), fewer rescue analgesia administrations (p < 0.01), and lower incidences of nausea/vomiting and postoperative agitation (p < 0.05). Group C exhibited superior outcomes to Group B in VAS scores (6, 12, 24, and 48 h), anesthetic consumption, and rescue analgesia metrics (p < 0.05), with no significant difference in adverse reactions (p > 0.05).ConclusionDexmedetomidine combined with ropivacaine for SNB improves postoperative analgesia, stabilizes intraoperative hemodynamics, reduces anesthetic usage and rescue analgesia needs, and lowers the incidence of adverse reactions in HICH craniotomy patients, making it a safe and effective analgesic strategy.Clinical trial registrationchictr.org.cn, identifier ChiCTR2500106043.